1996
DOI: 10.1007/s004010050468
|View full text |Cite
|
Sign up to set email alerts
|

Cellular distribution of the iron-binding protein lactotransferrin in the mesencephalon of Parkinson's disease cases

Abstract: Changes in the distribution of the iron-binding protein lactotransferrin have recently been described in the central nervous system during a variety of neurodegenerative disorders. To investigate whether lactotransferrin is associated with the neuropathological changes that characterize Parkinson's disease, we analyzed the distribution of this protein in the mesencephalon of neurologically normal individuals and patients affected with Parkinson's disease using quantitative immunohistochemical methods. High lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
66
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(68 citation statements)
references
References 46 publications
2
66
0
Order By: Relevance
“…Increased levels of lactoferrin in DA neurons resistant to degeneration in the brain of PD patients (Faucheux et al, 1995;Leveugle et al, 1996) and in the striatum of MPTP-intoxicated mice (Fillebeen et al, 2001) might be evidence of an attempt by the brain to minimize neurodegeneration. Because plasma levels of lactoferrin were reported to be inversely correlated with disease severity (Grau et al, 2001), therapeutic strategies that elevate lactoferrin plasma levels might be of interest for the treatment of PD patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased levels of lactoferrin in DA neurons resistant to degeneration in the brain of PD patients (Faucheux et al, 1995;Leveugle et al, 1996) and in the striatum of MPTP-intoxicated mice (Fillebeen et al, 2001) might be evidence of an attempt by the brain to minimize neurodegeneration. Because plasma levels of lactoferrin were reported to be inversely correlated with disease severity (Grau et al, 2001), therapeutic strategies that elevate lactoferrin plasma levels might be of interest for the treatment of PD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Despite substantial advances in the understanding of the pathomechanism in both inherited and sporadic forms of the disease , our knowledge of the cascade of events leading to DA cell demise remains incomplete. There are some lines of evidence that indicate that lactoferrin could possibly modulate PD progression: 1) the analysis of postmortem brain tissue sections of PD patients revealed that the immunolabeling of lactoferrin and lactoferrin receptors was augmented in DA neurons resistant to the disease process (Faucheux et al, 1995;Leveugle et al, 1996); 2) striatal lactoferrin mRNA transcripts were increased in a 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) mouse model of PD (Fillebeen et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…These effects of DA and other prooxidants on astroglial iron homeostasis may explain the discordant pattern of irodtransferrin receptor localization documented in the PD nigra and suggest that stressrelated trapping of non-transferrin-derived iron by astroglial mitochondria may be a key mechanism subserving the pathological accumulation of this metal in the basal ganglia of PD subjects. Based on the latter, we are currently investigating alternative iron transport mechanisms such as that mediated by lactoferrin and the lactoferrin receptor that are reportedly augmented in neurons, astrocytes, and blood vessels of PD-affected, ironladen neural tissues (Faucheux et al, 1995;Leveugle et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…The paraffin sections were cut at 2 m and subjected to immunohistochemistry as described previously (32). Complementary sections were demelanized using successive incubations with 0.25% potassium permanganate for 20 min followed by 1% oxalic acid and 1% potassium bisulfite for 4 min (33). The sections were incubated overnight at 4°C with polyclonal rabbit anti-human ubiquitin diluted 1:500 (Dako, DK), sheep anti-human AS diluted 1:200 (Abcam, UK), or anti-human 20 S proteasome antibody MCP20.…”
Section: Methodsmentioning
confidence: 99%